2001
DOI: 10.1021/ol0158516
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State and Time-Resolved Studies on Oxetane Cycloreversion Using (Thia)pyrylium Salts as Electron-Transfer Photosensitizers

Abstract: [reaction: see text] Cycloreversion of oxetane 1 is achieved using (thia)pyrylium salts as photosensitizers. RadicaI cation intermediates involved in the electron-transfer process have been detected using laser flash photolysis. The experimental results are consistent with the reaction taking place from the triplet excited state of the sensitizer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 15 publications
0
28
1
Order By: Relevance
“…Quantum chemical calculations (in the gas phase) predict that oxetanes cleave spontaneously after single electron donation or after single electron abstraction 24. Laser flash photolysis experiments by Falvey and co‐workers25 and Miranda et al26 recently provided experimental evidence that oxetanes do indeed split in the presence of various electron donors and acceptors in a light‐dependent reaction 27. So far, experiments which could clarify the function of the flavin coenzyme in (6‐4) photolyases and in particular the direction of the electron transfer within the enzyme active site are not reported.…”
Section: Methodsmentioning
confidence: 99%
“…Quantum chemical calculations (in the gas phase) predict that oxetanes cleave spontaneously after single electron donation or after single electron abstraction 24. Laser flash photolysis experiments by Falvey and co‐workers25 and Miranda et al26 recently provided experimental evidence that oxetanes do indeed split in the presence of various electron donors and acceptors in a light‐dependent reaction 27. So far, experiments which could clarify the function of the flavin coenzyme in (6‐4) photolyases and in particular the direction of the electron transfer within the enzyme active site are not reported.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25][26][27][28] Besides, it has been shown that, for diaryl-substituted oxetanes, splitting can also occur both from radical anions and cations. [29,30] The results obtained so far concern either the pyrimidine base alone or DNA hairpin model compounds; [31] no study has been realized on nucleoside-derived oxetanes.…”
mentioning
confidence: 99%
“…43 The radical cation of (E )-stilbene but not 1-phenylpropene was observed in laser flash photolysis experiments. The reaction is thought to occur from the triplet state of the photosensitizer.…”
Section: [2؉2] Cycloadditionsmentioning
confidence: 99%